PENGARUH RATING DAN CUSTOMER REVIEW TERHADAP MINAT BELI KONSUMEN DI E-COMMERCE SHOPEE PADA TOKO LOYAL LADS CLUB - Dinda Sukmawati; Leo Simanulang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of ratings and customer reviews on consumer purchase intention at the Loyal Lads Club store on the Shopee e-commerce platform. The rapid growth of e-commerce in Indonesia has intensified competition among local fashion brands, making social information such as ratings and customer reviews an important consideration in consumer decision-making. This research employed a quantitative approach with descriptive and verification methods. Data were collected through an online questionnaire from 100 respondents who had accessed or purchased Loyal Lads Club products, using purposive sampling. Multiple linear regression was applied to examine the partial and simultaneous effects of ratings and customer reviews on purchase intention. The findings indicate that ratings have a positive and significant effect on purchase intention, reflecting increased trust and perceived product quality. Customer reviews also show a positive and significant effect, strengthening consumer confidence and reducing perceived risk. Simultaneously, ratings and customer reviews significantly influence purchase intention, confirming the strategic role of electronic word of mouth in e-commerce marketing. The study implies that effective management of ratings and customer reviews is essential for enhancing the digital reputation and competitiveness of local brands on online marketplaces.